Homer 1a uncouples metabotropic glutamate receptor 5 from postsynaptic effectors - Kammermeier, Paul J; Worley, Paul F (Proceedings of the National Academy of Sciences - PNAS, 2007)
Metabotropic glutamate receptors (mGluRs) and Homer proteins play critical roles in neuronal functions including plasticity, nociception, epilepsy, and drug addiction. Furthermore, Homer proteins regulate mGluR1/5 function by acting as adapters and facilitating coupling to effectors such as the inositol triphosphate receptor. However, although Homer proteins and their interaction with mGluRs have been the subject of intense study, direct measurements of Homer-induced changes in postsynaptic mGluR-effector coupling have not been reported. This question was addressed here by examining glutamatergic excitatory postsynaptic currents (EPSCs) in rat autaptic hippocampal cultures. In most neurons, the group I mGluR agonist (S)-3,5-dihydroxyphenylglycine strongly inhibited the EPSC acutely. This modulation occurred postsynaptically, was mediated primarily by mGluR5, and was inositol triphosphate receptor-dependent. Expression of the dominant negative, immediate early form of Homer, Homer 1a, strongly reduced EPSC modulation, but the W24A mutant of Homer 1a, which cannot bind mGluRs, had no effect. (S)-3,5-dihydroxyphenylglycine-mediated intracellular calcium responses in the processes of Homer 1a-expressing neurons were reduced compared with those in Homer 1a W24A-expressing cells. However, neither the distribution of mGluR5 nor the modulation of somatic calcium channels was altered by Homer 1a expression. These data demonstrate that Homer 1a can reduce mGluR5 coupling to postsynaptic effectors without relying on large changes in the subcellular distribution of the receptor. Thus, alteration of mGluR signaling by changes in Homer protein expression may represent a viable mechanism for fine-tuning synaptic strength in neurons.